Trypanosoma brucei transferrin receptor: functional replacement of the GPI anchor with a transmembrane domain - Kabiri, Mostafa; Steverding, Dietmar (Molecular and biochemical parasitology, 2021)
The transferrin receptor of Trypanosoma brucei (TbTfR) is a heterodimer of a glycosylphosphatidylinositol (GPI)-anchored ESAG6 subunit and an ESAG7 subunit. To investigate whether the GPI-anchor is essential for the function of the TbTfR, an ESAG6 with a transmembrane domain instead of a GPI-anchor (ESAG6tmd) was inducibly expressed in bloodstream form trypanosomes. It is shown that the ESAG6tmd is able to dimerise with ESAG7 to form a TbTfR that can bind transferrin. Fractionation experiments clearly demonstrated that the transmembrane-anchored TbTfR is exclusively associated with the membrane fraction. No difference in the uptake of transferrin was observed between trypanosomes inducibly expressing a transmembrane-anchored TbTfR and trypanosomes inducibly expressing a GPI-anchored TbTfR. Differences in glycosylation pattern of ESAG6tmd and native ESAG6 may indicate different intracellular trafficking of transmembrane- and GPI-anchored TbTfRs. The findings suggest that the GPI-anchor is not essential for the function of the TbTfR in bloodstream forms of T. brucei.